The potency of cooperative integrated reading and composition in building chemistry students’ scientific literacy and self-regulated learning - Habiddin, Habiddin; Saputri, Cyndi Yanis; Santoso, Aman (Eclética Química, 2023)
The effect of the Cooperative Integrated Reading and Composition (CIRC) approach on scientific literacy and students’ regulated learning in colligative properties of solution was explored. The contribution of the CIRC approach was measured by investigating whether the improvement in scientific literacy and regulated learning of the CIRC students are more significant than the improvement for students with the Direct Instructional Teaching Method (DITM) after experiencing two different teaching approaches. Two groups of students (experiment and comparison) from a public senior high school in East Java, Indonesia, were involved. The experimental group experienced the colligative properties of solution with the CIRC teaching approach, while the comparison group experienced the DITM one. We found that scientific literacy and self-regulated learning of students with CIRC are higher than students with DITM, implying the potency of this approach to be applied to other chemistry topics. This study indicates that CIRC could be used to improve students’ scientific literacy and self-regulated learning for other chemistry topics. The implication of this study for teaching colligative properties of solution is also discussed.